2012
DOI: 10.1504/ijpm.2012.048878
|View full text |Cite
|
Sign up to set email alerts
|

Building procurement in a developing country: a comparison study between public and private sectors

Abstract: Public and private sectors have different work cultures that lead to different procurement usage. Changes in the industry have pushed the need to adopt new procurement systems. The present study explores the differences between public and private sectors' procurement systems in terms of usage and problems. A quantitative study was conducted on 141 industry players, covering contractors, consultants, and clients. Results showed that the traditional system is highly practiced by both sectors in the construction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Telgen et al (2007) observe that the demands on public procurement are greater and more varied than those on private sector procurement (p. 17). The significant variables differentiating procurement systems in the public and private sectors have been identified to be legal, risk, and operational factors ( Jaafar and Radzi, 2012). The objectives of the public sector and its procurement operations are wider than the singular objective of maximizing profit for a given company (Murray, 1999a;Larson, 2009), and it is in this way that devotion to the mission, vision, and values across the two sectors may diverge.…”
Section: Discussionmentioning
confidence: 99%
“…Telgen et al (2007) observe that the demands on public procurement are greater and more varied than those on private sector procurement (p. 17). The significant variables differentiating procurement systems in the public and private sectors have been identified to be legal, risk, and operational factors ( Jaafar and Radzi, 2012). The objectives of the public sector and its procurement operations are wider than the singular objective of maximizing profit for a given company (Murray, 1999a;Larson, 2009), and it is in this way that devotion to the mission, vision, and values across the two sectors may diverge.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the questionnaire survey done by Ting and Chin (2013), the most important selection criteria is the nature of work, which includes size, the level of complexity, type, and source of funding of the project. According to Jaafar and Radzi (2012), they concluded that the procurement system in Malaysia has not evolved greatly since the colonial British era. Many clients in the local industry prefer to choose procurement systems considered familiar, even though the criteria and purposes or every project are different.…”
Section: Standard Form Of Contractmentioning
confidence: 99%
“…Steinfeld et al (2015) find that public sector procurement practitioners perform and manage the occupational duty of “establish/uphold mission, vision, and values”, while an occupational duty with similar or general relative scope is completely absent from the BLS description of procurement. The study’s findings relate the performance and management of establishing/upholding mission, vision and values to the social responsibility aspect of public administration, seemingly the defining characteristic that makes the field esoteric, at least in its contemporary form, from related practice in the private sector such as business administration (Dahl and Lindblom, 1953; Wamsley and Zald, 1973; Perry and Rainey, 1988; Nutt, 2005; Bowman and Thompson, 2013) and public procurement from private sector purchasing and supply management (Murray, 1999; Telgen et al , 2007; Larson, 2009; Jaafar and Radzi, 2012).…”
Section: Introductionmentioning
confidence: 99%